Encyclopedia of educational theory and philosophy - Phillips, D. C. (Denis Charles), 1938- (Los Angeles, California : SAGE Reference, 2014)
The two-volume Encyclopedia of Educational Theory and Philosophy introduces readers to theories that have stood the test of time and those that have provided the historical foundation for the best of contemporary educational theory and practice. Drawing together a team of international scholars, this invaluable reference examines the global landscape of all the key theories and the theorists behind them and presents them in the context needed to understand their strengths and weaknesses.
vol. 1. A-K A-K-- vol. 2. L-Z ; index.
Includes bibliographical references and index.
Keywords: Education -- Philosophy -- Encyclopedias